Synthesis and Characterization of Superabsorbent Sodium Alginate-G-Poly (Potassium Acrylate) Hydrogels Prepared By Using Gamma Irradiation - Erizal Erizal; Fajar Lukitowati; Intan Oktaviani; Dhena Ria Barleany; Basril Abbas; Sudirman Umar (Jurnal Kimia dan Kemasan, 2017)
The aim of this research was to use gamma rays as sources for the preparation of superabsorbent hydrogels through radiation induced copolymerization. A series of superabsorbent hydrogels were prepared from aqueous solution containing partially neutralized acrylic acid (15%) with different sodium alginate (NaAlg) concentrations (0.5% to 1.5%) by ionizing gamma irradiation (10 kGy to 40 kGy) at room temperature. The effect of NaAlg concentration and irradiation doses on the water absorption behavior of the obtained hydrogels was investigated. The structural changes of hydrogels were characterized using Fourier Transform Infrared (FTIR) whereas the morphologies of hydrogels were examined using Scanning Electron Microscope (SEM). The results showed the swelling of hydrogel in water and NaCl solution increases with increasing NaAlg concentration and decreases with increasing irradiation dose up to 40 kGy. The extend of gel fraction increases as a function of NaAlg concentration. The results of FTIR analysis revealed that acrylic acid and sodium alginate had been successfully grafted, while SEM examination showed that the hydrogels demonstrated large numbers of pores.